Chloe & Cartoon. 1, When Chloe first met her cat, Cartoon - Tessier, Greg (Charmz, 2020)
Describes how the kitten Cartoon arrived in the Blin household as a Christmas gift for Chloe, then called Misty. Although Chloe's dad isn't thrilled with sharing the house with a cat, the family soon learns how to care for and understand Cartoon. Includes cat care tips.